Padrões de diversidade da família Lysmatidae: O que as análises espaciais e a modelagem de nicho nos revelam? - Cunha, Marina Calixto (2024)
Understanding the factors that shape species distribution and richness is crucial for studying ecological dynamics. Although diversity gradients are well-explored, the drivers of richness at large scales remain debated. This study aimed to comprehend the distribution patterns of the Lysmatidae family, how species relate to the marine environment, and which environmental variables are most relevant for structuring their niches. Another objective was to understand the niche dynamics among different lysmatids species and to assess whether the family supports the hypothesis of phylogenetic niche conservatism. It was observed that Lysmatidae has a circumtropical distribution, with species richness peaks in the tropical/subtropical transition zones in both hemispheres. The Western Atlantic Ocean and the Central Indo-Pacific region hold the highest diversity of Lysmatidae. The variables that most contributed to the family’s niches were temperature, salinity, bathymetry, and coral richness. Regarding niche dynamics, niche conservatism and cases of allopatry among species predominated. Our results suggest that Lysmatidae may be sensitive to the effects of climate change, given that temperature had a significant ecological influence on the structuring and stratification of shrimp communities, as well as coral richness. The family also exhibited cases of niche divergence, challenging the hypothesis of phylogenetic niche conservatism. The different configurations of niche dynamics observed, combined with the spatial patterns of evaluated sister species pairs, confirmed the possibility that both ecological and non-ecological processes could be responsible for the speciation events in this group.